Pengaruh Ukuran Perusahaan, Likuiditas, Leverage, Dan Aktivitas Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Perdagangan, Jasa Dan Investasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2019 - Adventius Gulo; Irmayanti Lumban Gaol; Monikha Tampubolon; Ike Rukmana Sari (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This research was conducted to test the effect of firm size, liquidity, leverage, and activity on profit growth in trading, service and investment sector companies listed on the Indonesia Stock Exchange (IDX) with a population of 164 companies for the period 2016-2019. The sample selection method used in this study is purposive sampling method, with a sample of 50 companies. The implementation of this research uses multiple linear regression analysis method with the SPSS 21 program. From the results of the research that has been done, it shows that simultaneously the independent variables consisting of firm size, liquidity, leverage and activity have a significant effect on the profit growth variable. Partially, it shows that firm size and liquidity have no and insignificant effect on profit growth. While the leverage variable has a negative and significant effect on profit growth and the activity variable has a positive and significant effect on profit growth. Keywords: Firm Size, Liquidity, Leverage, Activity, Profit Growth